Isolasi dan Implementasi Protein Bioaktif Kepah (Atactodea striata) Sebagai Bahan Obat Antibakteri - Tahirah Hasan; Abd. Rauf Patong; Abd. Wahid Wahab; M. Natsir Djide (Al-Kimia, 2014)
This study aimed to 1) determine the degree of saturation of ammonium sulfate right to extract and purify the bioactive protein from shells (Atactodea striata), 2) determine the fraction of active protein from shells (Atactodea striata) as a potential antibacterial. In this study used the Lowry method for determine protein concentration and agar diffusion method for antibacterial activity. Extraction of shells Atactodea striata was conducted by making use of buffer solution (0,1 M Tris-HCl of pH 8.3, 2 M NaCl, 0.01 M CaCl2, 1 % β-mercaptoethanol, and  0.5 % Triton X-100). Purification of proteins by  precipitation using ammonium sulfate at saturation level 30 %, 50 %, 70 %, and 90 %. The results showed that the protein concentration of the crude   extract is 41.6354 mg/mL. At fractionation rate of 0-90% saturation showed the highest concentration of protein found in fractions with 70% saturation level is 56.4184 mg/mL. The testing of antibacterial activity against Staphylococcus aureus showed that crude extracts and protein fractions Atactodea striata is considered effective as an antibacterial. The highest bioactivity during 24-hour incubation in protein fractions obtained by ammonium sulfate saturation level of 50% is 25.17 mm. Whereas the lowest activity was obtained at 90% saturation level is 14.05 mm. Bioactivity against Escherichia coli after incubation for 24 hours has the highest activity in the protein fraction with 30% ammonium sulfate saturation is 15.12 mm. Whereas the lowest activity was showed at 70% saturation level is 10.30 mm. After the observation was continued for 48 hours on both test bacteria, which formed a clear area becomes cloudy. It shows that the crude extract and fractions of protein tend to be bacteriostatic against Staphylococcus aureus and Escherichia coli.